Influence of Regional Erosion and Sedimentary Loading on Fault Activities in Active Fold-Thrust Belts: Insights From Discrete Element Simulation and the Southern and Central Longmen Shan Fold-Thrust Belt - Wu, Zhenyun; Yin, Hongwei; Li, Changsheng; Yang, Xiulei; Wang, Li; Wang, Fuyuan; Dong, Shaochun; Jia, Dong (Frontiers in Earth Science, 2021)
Four groups of discrete element models (DEMs) are set-up to simulate and analyze the influence of regional erosion and sedimentary loading on the formation and spatial-temporal evolution of faults in the southern and central Longmen Shan (LMS) active fold-thrust belt. The interior characteristics of faults in the southern and central LMS fold-thrust belt are also evaluated during the interaction of tectonic processes and surface processes according to the stress-strain analysis from DEM results. The results show that: (1) Synkinematic erosion promotes the reactivation of pre-existing faults in thrust wedges and also retards the formation and development of new incipient faults in the pre-wedges. Synkinematic sedimentation also delays the development of new incipient faults in the pre-wedge region by promoting the development of frontal thrust fault of thrust wedge, causing the thrust wedge in a supercritical stage with a relatively narrow wedge length; (2) The characteristics of erosion and sedimentation in the central and southern LMS have important influences on the activities of large faults which are extended into the deep detachment layer; (3) Besides differential erosion, the differential sedimentary loading may also be one of the important factors for the along-strike differential evolution of LMS fold-thrust belt. This kind of differential deposition may lead to differential fault activity and uplift in the interior thrust wedge and pre-wedge region in the central and southern LMS; (4) Compared to the northern LMS, the central LMS and southern LMS is more conducive to the occurrence of earthquakes, because of synkinematic sedimentation (such as the growth of Chengdu basin) has a greater blocking effect on the stress propagation and strain convergence on the fault planes of frontal faults of an active thrust wedge.